Analysis of The Influence of Curriculum Enrichment, Strategic Plan Design and Digital Guidance Model on Teaching-Learning Quality - Prayitno, Hadi; Achdijat Sulaeman; Citra Siwi Hanayanti; Dewi Febriyanti; Muhammad Ridhwan (Jurnal Sistim Informasi dan Teknologi, 2024)
This study aims to test and analyze the educational guidance model used in several schools in Indonesia. This study is descriptive and verification. The study uses a qualitative approach and is non-experimental. Data were collected through questionnaires and interviews. The results of the study indicate that there is support that is tailored for students with learning difficulties is needed to help and improve students' abilities in facing exams or evaluations. School management can use diagnostic tests, interventions in the learning and teaching process and structured guidance models to obtain good final results for student academics. The results of the study also show that diagnostic interventions are considered less able to solve problems comprehensively because diagnostic interventions do not involve students' personal conditions. It is important for school management to integrate the clinical model with other broader approaches. Limited resources and administrative tasks of the teacher team are obstacles and have been proven to hinder the effectiveness of work, so it is important for educational institutions to increase resource allocation. Continuous and structured educational evaluation helps improve the quality of teaching. Integration of various approaches and continuous evaluation is absolutely necessary to create better academic quality.